147 Use of Productivity Enhancing Technologies in Beef Steers Reduces Greenhouse Gas Emission Intensity. (8th October 2021) - Fortier, Sydney S; McAllister, Tim A; Lardner, Herbert; Alemu, Aklilu; Legesse, Getahun; Ominski, Kim; McKinnon, John J
Abstract: In the last decade, the cattle industry has witnessed increased demand from domestic and international markets for hormone and antibiotic free beef. However, the environmental consequences of switching from conventional production to "natural" beef have not been extensively examined. This study explored greenhouse gas (GHG) emissions estimated using a whole-farm model, Holos (www.agr.gc.ca/holos-ghg ) with model inputs from a 2-year replicated study in which calves were managed from weaning to finishing with 6 treatments based on body weight and feeding strategy. Treatments included Heavy (H), which were directly finished, Medium (M), which were backgrounded prior to finishing, and Light (L), which were backgrounded and then grazed during the summer before being placed on a finishing diet. Each treatment was subdivided into two management practices: Conventional (CON) in which productivity enhancing technologies (PETs) were used (ionophores, steroid implants and beta-adrenergic agonists) and Natural (NAT) in which PETs were removed. Emission intensity (kg CO2e kg -1 boneless beef) of HNAT was 17.3 to 20.1% higher than HCON, MNAT was 20.3 to 20.5% higher than MCON and LNAT were 11.5–12.6% higher than LCON treatment. Conventional treatments, using PET's, reduced GHG emissions, however grazing should be considered for its potential to store and promote carbon sequestration in perennial grasslands.